DAMPAK PENGGUNAAN A RTIFICIAL INTELLIGENCE TERHADAP EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH CHARIYATHAM SUKSA FOUNDATION SCHOOL THAILAND - Anang Mahfut; Mahmud Nasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inovative technology, particularly Artificial Intelligence (AI), has penetrated various fields, including education. This includes the learning process of Islamic Religious Education (PAI). This research aims to review in detail the impact of using AI implementation in enhancing the effectiveness of PAI learning at Chariyatham Suksa Foundation School Thailand. Its effectiveness is measured by the improvement of conceptual understanding regarding the use of AI. This study employs a descriptive qualitative approach with a case study method. The AI implementation examined includes data collection through an in-depth literature review. The process involves careful reading, precise investigation, and structured note-taking from various sources. The sources used include readings, journals, and relevant references. The collected data is then processed through filtering and critical analysis to be integrated into a theoretical framework. This process allows for the formation of clear conclusions based on strong theory. The tools utilized include interactive chatbots for answering subject matter questions, AI-based adaptive learning platforms for personalized learning adjustments, and automated assessment tools. From a long-term perspective, AI holds significant potential to become a vital tool in strengthening PAI learning. However, its optimal use depends on two crucial prerequisites wise implementation and perfect and appropriate integration into the existing curriculum and learning system